Communication at an online infertility expert forum: provider responses to patients' emotional and informational cues. (June 2015) - Aarts, J. W. M.; van Oers, A. M.; Faber, M. J.; Cohlen, B. J.; Nelen, W. L. D. M.; Kremer, J. A. M.; van Dulmen, A. M.
Abstract: Online patient-provider communication has become increasingly popular in fertility care. However, it is not known to what extent patients express cues or concerns and how providers respond. In this study, we investigated cues and responses that occur in online patient-provider communication at an infertility-specific expert forum. We extracted 106 threads from the multidisciplinary expert forum of two Dutch IVF clinics. We performed the following analyses: (1) thematic analysis of patients' questions; and (2) rating patients' emotional and informational cues and subsequent professionals' responses using an adaptation of the validated Medical Interview Aural Rating Scale. Frequencies of themes, frequencies of cues and responses, and sequences (what cue is followed by what response) were extracted. Sixty-five infertile patients and 19 providers participated. The most common themes included medication and lifestyle. Patients gave more informational than emotional cues (106 versus 64). Responses to informational cues were mostly adequate (61%). The most common response to emotional cues was empathic acknowledgment (72%). Results indicate that an online expert forum could have a positive effect on patient outcomes, which should guide future research. Offering infertile patients an expert forum to communicate with providers can be a promising supplement to usual care in both providing information and addressing patients' concerns.